Bruton tyrosine kinase inhibitors for Waldenström macroglobulinemia: A review. (December 2021) - Moore, Donald C
Objective: The objective of this review is to evaluate the available evidence for the Bruton tyrosine kinase inhibitors in the treatment of Waldenström macroglobulinemia. Data sources: A search of the PubMed database was conducted using the following search terms: ibrutinib, PCI-32765, acalabrutinib, ACP-196, zanubrutinib, BGB-3111, and Waldenström macroglobulinemia . Prospective clinical trials evaluating the efficacy and safety of ibrutinib, acalabrutinib, and zanubrutinib in patients with Waldenström macroglobulinemia were evaluated. Abstracts from the American Society of Hematology and American Society of Clinical Oncology annual meetings were reviewed as well as the prescribing information for each drug. Data summary: The first-generation Bruton tyrosine kinase inhibitor ibrutinib received Food and Drug Administration approval for Waldenström macroglobulinemia in 2015; this was the first drug approved for this rare condition. Ibrutinib has been evaluated as monotherapy and in combination with rituximab for the treatment of Waldenström macroglobulinemia. Since then, second-generation Bruton tyrosine kinase inhibitors, acalabrutinib and zanubrutinib, have been evaluated in prospective clinical trials for the treatment of Waldenström macroglobulinemia. All three agents have demonstrated high overall response rates and durable responses. Conclusion: Bruton tyrosine kinase inhibitors have demonstrated significant clinical activity in the treatment of Waldenström macroglobulinemia, both in treatment naïve as well as the relapsed/refractory patient populations.